A cross-cultural comparison of the consideration and use of politeness strategies in making spoken invitations between English and Vietnamese speakers - Nguyễn, Ngọc Huệ (2019)
Đồng ý về việc phục vụ đọc trực tuyến, không đồng ý về việc chép file, cho photo 50% tài liệu; References: p. 61 - 65; Master thesis of Thu Dau Mot University. Major: English language; Code: 8220201; 5 chapters: Introduction; literature review; methodology; findings and discussion; conclusion